The Impact of Digitalization on Changing People's Economic Patterns - Moh. Yamin Darsyah (STEBIS Bina Mandiri, 2025)
The development of digital technology in recent years has brought fundamental changes to people's economic activities. This research aims to analyze the impact of digitalization on changes in people's economic patterns, including consumption, transactions, financial management, business activities, and work patterns and income. The research uses a qualitative approach, employing the library research method by examining various reputable scientific literature, particularly international journals indexed in Scopus over the last five years. Research data were obtained through systematic searches of scientific articles, books, and research reports relevant to economic digitalization. The study's results show that digitalization has significantly changed people's economic behavior. In the consumption aspect, there is a shift from conventional shopping to digital shopping through e-commerce platforms. In terms of transactions, the use of digital payments, such as e-wallets and QRIS, is increasing, forming more efficient economic habits. Digitalization also affects household financial management patterns through easy access to digital financial services. On the other hand, digitalization encourages transformation in MSMEs and creates new forms of work through the gig economy. However, the impact of digitalization is not always evenly distributed, as there remains a gap in access to technology and digital literacy across society. This study concludes that digitalization plays a vital role in shaping the modern economic landscape. Still, inclusive policies are needed so that the benefits are felt more fairly and equitably.